1999
DOI: 10.1007/bf02237127
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, controlled trial of low molecular weight heparin vs. no deep vein thrombosis prophylaxis for major colon and rectal surgery in Asian patients

Abstract: Deep venous thrombosis prophylaxis is needed in Asian patients undergoing major colorectal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
1
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 22 publications
2
77
1
2
Order By: Relevance
“…These results are comparable to those of a prospective cohort study evaluating the safety of FPX for the prevention of VTE in Japanese patients undergoing CRC surgery, which reported incidences of 0.81 and 9.5%, respectively [10]. In several studies evaluating the safety of LMWH for the prevention of VTE after CRC surgery, the incidence of major bleeding and minor bleeding was reported to be 0.89-2.7% and 4.5-8.0%, respectively [13,14,15], similar to our results. These results suggest that FPX is comparable to LMWH in terms of prevention of symptomatic VTE and postoperative bleeding in patients undergoing CRC surgery.…”
Section: Discussionmentioning
confidence: 99%
“…These results are comparable to those of a prospective cohort study evaluating the safety of FPX for the prevention of VTE in Japanese patients undergoing CRC surgery, which reported incidences of 0.81 and 9.5%, respectively [10]. In several studies evaluating the safety of LMWH for the prevention of VTE after CRC surgery, the incidence of major bleeding and minor bleeding was reported to be 0.89-2.7% and 4.5-8.0%, respectively [13,14,15], similar to our results. These results suggest that FPX is comparable to LMWH in terms of prevention of symptomatic VTE and postoperative bleeding in patients undergoing CRC surgery.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only five small open studies have evaluated a prophylactic method in Asian patients. 18,[31][32][33][34] These studies were small in size and the beneficial effect of treatment was in general not statistically significant, but all showed that prophylaxis could reduce the rate of venous thromboembolism to some extent. Although these data should be confirmed in larger well-conducted multicenter studies, we believe that there is no reason why the benefit of thromboprophylaxis, well documented in the West, 4 should not also be achieved in Asian patients.…”
Section: Discussionmentioning
confidence: 99%
“…The autopsy prevalence of PE was lower in Japanese (0.7%) compared with North Americans (15%) [7]. Among Asians in Singapore, DVT prevalence among hospitalized patients (15.8 per 10,000 admissions) [8] and incidences following total knee replacement (14%) [9], major colorectal surgery (3%) [10] and cranial procedures (5%) [11] were lower compared with Caucasian data. This has led to the suggestion that DVT after stroke in Asians is not common.…”
Section: Introductionmentioning
confidence: 99%